2013
DOI: 10.1038/cddis.2013.182
|View full text |Cite
|
Sign up to set email alerts
|

Wentilactone B induces G2/M phase arrest and apoptosis via the Ras/Raf/MAPK signaling pathway in human hepatoma SMMC-7721 cells

Abstract: Hepatocellular carcinoma (HCC) is generally acknowledged as the most common primary malignant tumor, and it is known to be resistant to conventional chemotherapy. Wentilactone B (WB), a tetranorditerpenoid derivative extracted from the marine algae-derived endophytic fungus Aspergillus wentii EN-48, has been shown to trigger apoptosis and inhibit metastasis in HCC cell lines. However, the mechanisms of its antitumor activity remain to be elucidated. We report here that WB could significantly induce cell cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 50 publications
3
65
0
Order By: Relevance
“…MAPKs mainly consists of ERK1/2, c-Jun N-terminal kinases (JNKs) and p38 MAPKs. It has been confirmed that inactivation of ERK1/2 and activation of p38 are involved in triggering mitochondrial-mediated apoptosis in cancer cells [25,26]. In accordance with these findings, we here found that YYJ18 inhibited phosphorylation of ERK1/2 in CNE2 cells in a dose- and time-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…MAPKs mainly consists of ERK1/2, c-Jun N-terminal kinases (JNKs) and p38 MAPKs. It has been confirmed that inactivation of ERK1/2 and activation of p38 are involved in triggering mitochondrial-mediated apoptosis in cancer cells [25,26]. In accordance with these findings, we here found that YYJ18 inhibited phosphorylation of ERK1/2 in CNE2 cells in a dose- and time-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…13, 14, 15 We report here that EN-48-56, known as Wentilactone A (WA), exerts a significantly inhibitory effect on the lung carcinoma cell lines NCI-H460 and NCI-H446 without markedly inhibiting the proliferation of normal HUVECs. Furthermore, WA has the opposite molecular mechanism to EGFR inhibitors.…”
mentioning
confidence: 97%
“…The resultant increase in the proportion of cells arrested at the G 2 /M phase could promote either cell death or survival. For example, in some types of cancer cells, the cell cycle is arrested at G 2 /M phase in response to insults from anticancer drugs (54, 55). In the previous study, the antioxidants were used to protect blastoderm cells from peroxidative degradation during cold storage indicating that oxidative stress during dormancy could cause DNA double‐strand breaks, which could be critical to cell cycle arrest in blastoderm cells (56).…”
Section: Discussionmentioning
confidence: 99%